Nitroimidazole Action in Entamoeba histolytica: A Central Role for Thioredoxin Reductase - Leitsch, David; Kolarich, Daniel; Wilson, Iain B. H; Altmann, Friedrich; Duchêne, Michael (PLOS Biology, 2007)
Metronidazole is used for treatment of infections with microaerophilic protist parasites. Here, a new model of metronidazole activation is proposed, with a central role for thioredoxin reductase.